Characteristics of the demand for cut flowers and seasonal flowers in Argentina - Fernandez Acevedo, Victoria (2021)
Argentina has great potential in the production of floricultural products. Despite this, its products are mainly destined for the domestic market, which is highly fluctuating, not only because they are considered luxury products, but also because they are an easily substitutable product, dependent on customs, fashion cycles, and the competition with a wide variety of products. Little is known about the characteristics of the demand for these products; therefore the objective of this work is to carry out a first analysis of floricultural products from the point of view of consumers, in order to know their preference and purchasing tastes in a society of changing consumption. For this, digital surveys were carried out, through the Google Forms platform, to different residents of Argentina, consulting on preferences and characteristics of the consumption of cut flowers and seasonal seedlings. Among the most relevant results obtained: there is a trend towards the consumption of potted plants compared to cut flowers and the main limitation of consumption is the price. Current cut flower products may not satisfy consumer requirements, mainly due to the lack of fragance. Seasonal seedlings and potted plants seem to position themselves as the preferred product, mainly due to the durability / price ratio and current social trends, showing a generational relegation against the cut flowers.